Tindak Tutur Perlokusi Representatif dalam Acara “Lapor, Pak!” Trans 7 - Dwi, Tifani Dwi Kurniavid; Novitasari, Lusy; Purnama, Ardian Pitra Satya (LEKSIS: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
Representative speech acts are actions that use speech to bind the speech partner to the truth being conveyed. This research aims to describe the form and function of representative perlocutionary speech acts in the event "Report, Sir!" Trans 7. This research uses a qualitative descriptive method. Data collection uses content analysis techniques (Nurgiyantoro, 1995). Content analysis techniques consist of finding data, data classification, and data analysis. Data analysis uses data reduction techniques (unit identification and coding), data categorization, and synthesis. Based on the results of the research, the forms and functions of speech acts that are often spoken are the form of speech acts demanding 26 data and the function of speech acts demanding 26 data, the form of speech acts stating 18 data and the function of speech acts stating 18 data, and the form of speech acts reports 15 data and the speech act function reports 15 data. The forms and functions of speech acts that are rarely spoken are that the form of the speech act mentions 1 data and the function of the speech act states 1 data, the form of the speech act shows 2 data and the function of the speech act shows 2 data. The theory used in this research is Rustono's theory.